2019
DOI: 10.5539/jas.v11n5p152
|View full text |Cite
|
Sign up to set email alerts
|

Dry Mass Accumulation, Nutrients and Decomposition of Cover Plants

Abstract: The use of cover crops is an important strategy for soil management in the Brazilian Cerrado to improve no-tillage (NT) systems. For this, it is necessary know the potential of cover crop species for biomass production, nutrient cycling, and persistence of residues on the soil surface in soils and climatic conditions of this biome. Thus, the experiment was developed to evaluate the agronomic potential of cover crops cultivated on an Oxisol (Latossolo Amarelo) in the Cerrado of Piauí, Brazil. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
(25 reference statements)
1
5
1
3
Order By: Relevance
“…Microbial biomass carbon (mg 100 g -1 ) for 105 days of incubation after incorporation of grasses and legume straw in an Oxisol. The straw of Pennisetum glaucum (PG) and Brachiaria brizantha (BB) have a C/N ratio > 30.0 (Table 1) and approximately 40% of the accumulated phytomass of Pennisetum glaucum is from the stem, which consists of lignified tissues with a higher C/N ratio than the leaves (SOUSA et al, 2019). This means that the N immobilization process predominates over N mineralization (MOREIRA;SIQUEIRA, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial biomass carbon (mg 100 g -1 ) for 105 days of incubation after incorporation of grasses and legume straw in an Oxisol. The straw of Pennisetum glaucum (PG) and Brachiaria brizantha (BB) have a C/N ratio > 30.0 (Table 1) and approximately 40% of the accumulated phytomass of Pennisetum glaucum is from the stem, which consists of lignified tissues with a higher C/N ratio than the leaves (SOUSA et al, 2019). This means that the N immobilization process predominates over N mineralization (MOREIRA;SIQUEIRA, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Knowing the temporal dynamics of N mineralization or immobilization of the different cover crops it is important to manage the agricultural systems in the Cerrado. It is also necessary to choose the correct species to be used and the ideal moment to sow the following crop so that the decomposition and release of nutrients by the cover plants can happen in the period of greater demand by the following crop (SOUSA et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A maior disponibilidade de N do solo resulta em maiores processos de mineralização da matéria orgânica. Espécies da família Fabaceae, por possuírem alto teor de N em seus tecidos vegetais, consequentemente apresentam baixa relação C/N (SOUSA et al, 2019). WANG et al (2014), esclarecem que relações C/N maiores que 30 indicam a imobilização de N no solo, enquanto valores menores que 20 favorecem a mineralização e maior disponibilidade de N para as plantas.…”
Section: Discussionunclassified
“…Maize intercropped with Urochloa contribute residues to the surrounding system that have a high C/N ratio and high lignin quantity compared to the residues derived from soybean/ millet crops, which allows the straw greater perenniality (GARCIA et al, 2014;SOUSA et al, 2019). In this sense, when observing the trends of the results presented here, which were processed through uni and multivariate statistical analyses showed that the area without recent history of soil tillage which had the CLI system introduced 4 years ago, was most efficient in increasing soil C (121 t/ha) and N (3.4 t/ha) (Table 2), since it is linked to the largest number of studied C and N response variables (Figure 4).…”
Section: Attributesmentioning
confidence: 99%